Augmented Reality for Islamic Education: Enhancing Qur’an Learning in Nigeria - Moses Adeolu AGOI; Oluwakemi Racheal OSHINOWO; Bukola Abosede FOLARANMI; Khairuddin Khairuddin; Hendri Hermawan Adinugraha (Abdurrauf Journal of Education and Islamic Studies, 2026)
This research investigates the transformative potential of Augmented Reality (AR) to enhance Qur’anic education by improving visualization, learner engagement, and experiential understanding. It specifically addresses the pedagogical gap between traditional rote memorization and the interactive learning preferences of students in the digital era. The research employs a systematic literature review, analyzing peer-reviewed articles and empirical studies published between 2020 and 2025. The analysis focuses on instructional design, learning outcomes, and technological platforms within Islamic educational contexts to identify current trends and research gaps. The findings indicate that AR-supported environments significantly increase learner motivation and cognitive engagement compared to conventional methods. Students utilizing AR show marked improvements in Tajw?d accuracy and narrative retention, with studies reporting scores up to fifteen percentage points higher than traditional learners. Interactive 3D Arabic letters and contextual visualizations facilitate effective multisensory learning. However, implementation faces challenges related to infrastructure, teacher competence, and the need for Shariah-compliant content verification. AR serves as a strategic adjunct to traditional instruction, modernizing pedagogy while maintaining spiritual values. Successful integration requires interdisciplinary collaboration among scholars and technologists to ensure authentic, ethically grounded content and institutional support for sustainable implementation. This research addresses a critical gap in the existing literature by focusing specifically on AR applications for Qur’anic literacy and Tajw?d, and provides a contemporary synthesis of empirical evidence to guide digital transformation in religious education.